2020
DOI: 10.18485/aeletters.2020.5.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Fault Analysis of Gearboxes in Open Pit Mine

Abstract: The paper presents the results of testing gearboxes in coal open pit mine which have been damaged by various mechanisms. Gearboxes, as constituents of belt conveyors, bucket-wheel excavators and bucket chain excavators and spreaders, are the most loaded segments of drive units the functionality of which affects the operation of complete coal and overburden systems. Therefore, special attention has to be paid to their condition so that the analysis of relevant condition indicators could lead to correct conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Statistical data show that in the gear transmission elements, newly manufactured, most damages appear on gears, followed by failures of bearings, while failures of other parts of the power transmitters are significantly less common. That is the primary reason why many researchers paid special attention to the phenomena of the damage and destruction of gear teeth, their character, the causes for their appearance and the possibility of eliminating those causes [ 1 , 2 , 3 , 4 , 5 ]. A much smaller number of researchers have studied the possibility of repairing those damages, namely, extending the service life of gears and increasing their safety and reliability in operation.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical data show that in the gear transmission elements, newly manufactured, most damages appear on gears, followed by failures of bearings, while failures of other parts of the power transmitters are significantly less common. That is the primary reason why many researchers paid special attention to the phenomena of the damage and destruction of gear teeth, their character, the causes for their appearance and the possibility of eliminating those causes [ 1 , 2 , 3 , 4 , 5 ]. A much smaller number of researchers have studied the possibility of repairing those damages, namely, extending the service life of gears and increasing their safety and reliability in operation.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are the regeneration of forging tools and parts of the forging industry [ 11 , 12 , 13 , 14 , 15 ], where it was pointed out that the function of the damaged part can be restored very quickly and thus achieve savings in terms of downtime, savings on material and energy, employment etc. Similar principles are emphasized in papers [ 16 , 17 ], on examples of construction machinery parts, in works [ 18 , 19 ] on examples of heavy mining equipment parts, as well as responsible parts of machine constructions, such as gears, whether they are the author’s own research [ 20 , 21 , 22 ] or research by other authors [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In all the mentioned research, it has been shown that hard-facing achieved at least the same characteristics of the applied welds in comparison to the basic materials, while it is often the case that their resistance is even higher.…”
Section: Introductionmentioning
confidence: 74%
“…Power losses in gear transmission vary extensively, which depends on many influencing factors, the most important of which are the type of material of meshed gears, geometry of worm pair, gear velocity, type and viscosity of lubricating oil, load, shape of the worm, operating temperature, etc. [10][11][12][13][14][15][16][17]. Based on DIN3996 standard [18], power losses in worm gearbox can be divided into load-dependant losses (mechanical losses) and load-independent losses.…”
Section: Introductionmentioning
confidence: 99%